Preserving Indigenous Heritage: The Right to Effective Participation and Sámi Languages - Palmer, Nerys Louise (2024)
Central to Indigenous Peoples’ right to self-determination, the right to effective participation and free, prior, and informed consent are means to which they may exercise autonomy over matters directly concerning them. For the Sámi People in Norway, the State has adopted all relevant human rights instruments to ensure the realisation of these rights. However, the effectiveness of their application may be contended, with legislative action not necessarily matching Norway’s human rights commitments or Sámi rights-holders expectations. This study seeks to address what makes effective participation ‘effective’ in this context, through evaluating the level of participation enjoyed by Sámi representatives in decision-making processes. In particular, this study follows the 2024 amendments to Chapter three of the Sámi Act on Sámi languages, central to the advancement of Sámi rights in general, with language embedded in the functioning of the Sámi Parliament, Sámi culture, identity, and carried through traditional economic activities such as reindeer herding. Underscoring the level of Sámi participation is the long-lasting effects of historical assimilation policies, and whether this interferes with their involvement in decision-making processes. Relating to the declining rate of Sámi languages, and Indigenous languages in general, the International Decade on Indigenous Languages was declared from 2022-2032. As a Member State, Norway has developed an Action Plan for the Decade, setting out goals and aims for Sámi language development. Under the umbrella of recent linguistic developments, this thesis addresses the extent to which Sámi People enjoy effective participation in determining language policy in Norway, and whether recent measures are sufficient to address the critical status of Sámi languages, language speakers, and Indigenous languages more generally.